Kepatuhan Pajak Kendaraan Bermotor di Kabupaten Pati - Farida Rahmawati; Nita Andriyani Budiman; Retno Tri Handayani (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This study aims to determine the effect of tax awareness, moral obligation, level of education, financial condition, mobile SAMSAT, and tax sanctions on motor vehicle tax compliance. This research was conducted in the Mobile SAMSAT area of Pati Regency. Respondents in this study amounted to 410 motor vehicle taxpayers using purposive sampling method with primary data. Data analysis in this study used multiple linear regression tests with the SPSS version 25 statistical tool. The results of this study indicate that tax awareness has a positive effect on tax compliance, moral obligation has a positive effect on tax compliance, education level has no effect on tax compliance, financial condition has a positive effect on tax compliance, mobile SAMSAT has no effect on tax compliance, and tax sanctions have a positive effect on tax compliance.